Settlement Limits of Discounting Bank’s Right Across Reversing Entry to his debit in the Bank Account of the Discounted side - الشماع فائق محمود (Journal of Legal Sciences, 2019)
In order to facilitate the accounting procedure and accelerate its achievement, commercial banks used to follow reversing entry style in agent’s account opened with them, to settle its debits caused by non-payment of the discounted commercial paper value. The question was raised about: the legal importance to such method for settling the discounting bank debits, particularly when the bank account of the discounted side was debtor and not creditor, as the case of discounted party under bankruptcy. It is noted that the Jordanian trade legislations is totally silent in this regard, as well as the other trade legislations which are frankly considering the reversing entry as an organizer for deleting the trust entry which was previously mentioned in the account, they are also silent to declare consequences caused by such deletion for the commercial paper that was acquired through possessory endorsement so the right of this bank will focus exclusively on bankruptcy contribution of the discounted side, or in spite of the reversing entry the discounting bank would keep the discounting paper, and have the right to recourse against payment sureties. Dose the discounting bank has the choice in these two options to regain its debts? Or can it combine the two methods if necessary? The answers for these queries shall be the core study of our research. The will demonstrate the impacts and consequences of reversing entry in the bank account for discounted side whether it is wealthy or bankrupt.